Combining differentiating and integrating over time to sustain multiple institutional logics: a case study of a higher education institution - Jiang, Ye; Zhang, Xiaojun (Frontiers in Psychology, 2023)
To understand how organizations adopt varying configurations of differentiating (i.e., compartmentalizing logics into different subunits or roles) and integrating (i.e., combining logics to highlight synergies) over time to navigate logic contestations and extract logic complementarities for organizational innovation, we conduct a 15-year indepth longitudinal case study of a higher education institution to examine how it devised innovative hybrid practices to manage and support college student development.By employing the grounded theory method, we develop a four-stage process model of the varying configurations of differentiating and integrating that expounds on how two contested logics are sustained and exploited over time. We assert that selective bridging the instrumental use of one logic enables some practices of one logic to be selectively integrated with the other, while irreconcilable practices remain differentiated to play their respective roles, is vital in allowing organizations to leverage respective advantages in combining differentiating and integrating over time. Further, we show that combining integrating and differentiating features simultaneously transforms contested logics into compatible and complementary, offering a novel way for logic hybridization. These findings advance the understanding of how organizations can differentiate and integrate contested logics over time through a dynamic and paradoxical view, thus being manageable and manipulated for organizational innovation.